2012
DOI: 10.1021/cg3010272
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, Characterizations, and Properties of Five Interpenetrating Complexes Based on 1,4-Benzenedicarboxylic Acid and a Series of Benzimidazole-Based Linkers

Abstract: Five interesting interpenetrating networks, namely, [Co(p-bdc)(beb) 0.5 ] n (1), {[Co(p-bdc)(bmb)]·H 2 O} n (2), {[Co(pbdc)(bmp)]·H 2 O} n (3), {[Zn(p-bdc)(bmp)]·H 2 O} n (4), and [Zn 2 (pbdc) 2 (bmp)(H 2 O) 2 ] n (5) [p-H 2 bdc = 1,4-benzenedicarboxylic acid, beb = 1,4-bis(2-ethylbenzimidazol-1-ylmethyl)benzene, bmb = 1,4-bis(2-methylbenzimidazol-1-ylmethyl)benzene, and bmp = 1,5-bis(2-methylbenzimidazol) pentane], have been synthesized by employing mixed ligands of various benzimidazole-based ligands with p-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…Each Cd atom in 4 is bridged by dna into a 1D zig-zag chain along the a-axis (Fig. 6b), and is similar to the previously reported complex [Zn 2 (p-bdc) 2 (bmp)(H 2 O) 2 ] n obtained from reaction of Zn(NO 3 ) 2 Á6H 2 O with p-bdc ligand, [11,12] where p-H 2 bdc ¼ 1,4-benzenedicarboxylic acid and bmp ¼ 1,5-bis(2methylbenzimidazol) pentane). The adjacent 1D chains are further connected by the long dpp ligands resulting in the formation of the 3D framework (Fig.…”
Section: Crystal Structure Ofsupporting
confidence: 85%
“…Each Cd atom in 4 is bridged by dna into a 1D zig-zag chain along the a-axis (Fig. 6b), and is similar to the previously reported complex [Zn 2 (p-bdc) 2 (bmp)(H 2 O) 2 ] n obtained from reaction of Zn(NO 3 ) 2 Á6H 2 O with p-bdc ligand, [11,12] where p-H 2 bdc ¼ 1,4-benzenedicarboxylic acid and bmp ¼ 1,5-bis(2methylbenzimidazol) pentane). The adjacent 1D chains are further connected by the long dpp ligands resulting in the formation of the 3D framework (Fig.…”
Section: Crystal Structure Ofsupporting
confidence: 85%
“…[3][4][5] Among diverse entangled MOFs, interpenetration is the most familiar phenomenon. To date, considerable efforts have been invested in interpenetrating MOFs and a great many interpenetrating networks have been reported by many groups [6][7][8][9] and some comprehensive reviews have been made by Robson, Batten, and Ciani et al [10][11][12] Summarizing from the large amount of reported works, we can draw a conclusion that long and low steric hindrance ligands will lead to larger voids that may result in high-fold interpenetrating structures. [13] Therefore, the effective strategy for constructing interpenetrating MOFs is to use long and low steric hindrance ligands.…”
Section: Introductionmentioning
confidence: 93%
“…6(b), an intense emission occurs at 400 nm with the excitation wavelength at 320 nm. In comparison, the free L ligand shows an emission at 428 nm upon excitation at 300-350 nm at room temperature (Tzeng et al, 2008) and free benzene-1,4-dicarboxylic acid shows an emission at 369 nm with an excitation at 331 nm (Guo et al, 2012). Accordingly, the emission in (1) is most likely to originate from the L ligand through atransition, given the significant blue shift (28 nm) on going from L to (1) (Guo et al, 2012).…”
Section: Figurementioning
confidence: 99%